High hole mobility of a semi-conductive alumina/nano-carbon ceramic composite fabricated by gel-casting and reductive sintering. Issue 4 (April 2019) - Xin, Yunzi; Kumazawa, Tomoshi; Fuji, Masayoshi; Shirai, Takashi
Abstract: Semi-conductive alumina/nano-carbon ceramic composite with high hole mobility is fabricated by gel-casting and reductive sintering. The hole mobility observed in the fabricated composite is 80-fold higher than the previously reported alumina/graphene composite. Such superior semi-conductive performance of the alumina/nano-carbon composite can be attributed to the homogenous electrically conductive path induced by nano-carbon with well-controlled graphite structure formed during fabrication process. In addition, the influence of sintering temperature on the structure of nano-carbon as well as its relation to the semi-conductive properties of composite are systemically investigated.